1Dand 2D Ξb and Λb baryons *Supported by the Fundamental Research Funds for the Central Universities (016MS133), Natural Science Foundation of HeBei Province (A2018502124). (1st September 2022) - Yu 于, Guo-Liang 国梁; Wang 王, Zhi-Gang 志刚; Wang 王, Xiu-Wu 修武
Abstract: Recently, scientists have achieved significant progress in experiments searching for excited and baryons such as, , , , , , and . Motivated by these achievements, we systematically analyze the and states of and baryons using the method of quantum chromodynamics sum rules. By constructing three types of interpolating currents, we calculate the masses and pole residues of these heavy baryons with different excitation modes:, , and . Subsequently, we decode the inner structures of, , , and and favor assigning these states as the baryons with the quantum numbers and, , , and, respectively. In addition, the predictions for the masses and pole residues of the other and and baryons in this paper will be useful for studying D -wave bottom baryons in the future.